The Effect of a Flipped Classroom Approach Based on the Rahmatan Lil 'Alamin Project in Enhancing Speaking Skills of Senior High School Students - Riskiyah, Farika; Kholisin; Abdul Adzim Irsyad (Institut Agama Islam Negeri Curup, 2025)
This study aimed to examine the effect of the flipped classroom approach based on the students’ project Rahma for the World in enhancing the speaking skills of eleventh-grade students at Nour Al Uloom Islamic Secondary School. A descriptive quantitative experimental method was employed using a one-group pretest–posttest design. The findings revealed that the flipped classroom approach integrated with the students’ project had a statistically significant impact on improving students’ speaking skills. The mean post-test score (16.43) was higher than the mean pre-test score (12.86). The Mann–Whitney U test indicated a significance value (Asymp. Sig. (2-tailed)) of 0.000, which is less than 0.05. Therefore, the null hypothesis (H₀) was rejected, and the alternative hypothesis (Hₐ) was accepted.